Streptococcus dysgalactiae: An emerging pathogen of fishes and mammals - Mohamed Abdelsalam; Abdellatif Asheg; Alaa Eldin Eissa (International Journal of Veterinary Science and Medicine, 2013)
Streptococcus dysgalactiae subsp. dysgalactiae (GCSD) has gained special interest of aquatic health experts throughout the past few years due to its interesting veterinary and public health importance. Increasing records of GCSD infections in farmed fishes have been documented through diverse worldwide aquatic habitats in Japan, China, Malaysia, Indonesia, Taiwan and Brazil. Despite the intraspecies/interspecies dynamic spread of fish GCSD, yet, the genetic basis of its virulence remains unknown. This gap in knowledge is the main reason behind inability to develop a competent vaccine to control the disease in aquatic animals. However, the authors have concluded that the virulence of GCSD is mainly based on its cell surface properties such as high hemagglutination and hydrophobic properties which determine the main adhesive/invasive pathogenic mechanism of the pathogen where GCSD isolates were able to adhere to and invade fish epithelial cell line in vitro. Most recently, the molecular pathogenesis investigations have revealed that, serum opacity factor [SOF], superantigen and streptolysin S genes might be the most important virulence factors that have contributed to the swift propagation of streptococcal infection among aquatic and mammalian species. In conclusion, the current research based review has emphasized the current knowledge gap in epidemiology and control of fish GCSD. To bridge this current gap, a swift future development of high tech/accurate molecular research is highly needed to better understand the pathogenic mechanisms of GCSD.